Trichoderma spp. decrease Fusarium root rot in common bean - Teixeira,Hudson (2012)
The effectiveness of six Trichoderma-based commercial products (TCP) in controlling Fusarium root rot (FRR) in common bean was assessed under field conditions. Three TCP, used for seed treatment or applied in the furrow, increased seedling emergence as much as the fungicide fludioxonil. FRR incidence was not affected, but all TCP and fludioxonil reduced the disease severity, compared to control. Application of Trichoderma-based products was as effective as that of fludioxonil in FRR management.